2006
DOI: 10.1116/1.2338045
|View full text |Cite
|
Sign up to set email alerts
|

Neutron irradiation effects in p-GaN

Abstract: Electrical properties, admittance, and microcathodoluminescence spectra are compared for p-GaN samples grown by hydride vapor phase epitaxy ͑HVPE͒ and by molecular beam epitaxy ͑MBE͒. The former are characterized by a high 300 K hole concentration and a weak temperature dependence of conductivity. The latter samples show strongly temperature-activated conductivity due to ionization of Mg acceptors. The main effects of neutron irradiation were similar for the p-HVPE and the p-MBE materials: a compensation of p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Comparison between Schottky diodes and high electron-mobility transistors suggests that the degradation in both types of devices is predominantly due to carrier removal and mobility degradation caused by radiation-induced defect centers in the crystal lattice, with interface disorder playing a relatively insignificant part in overall device degradation. [145][146][147][148][149][150][151][152][153][154][155] In summary, the main effects of radiation damage in GaN-based HEMTs can be noted as follows:…”
Section: Ecs Journal Of Solid State Science and Technology 5 (2) Q35mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between Schottky diodes and high electron-mobility transistors suggests that the degradation in both types of devices is predominantly due to carrier removal and mobility degradation caused by radiation-induced defect centers in the crystal lattice, with interface disorder playing a relatively insignificant part in overall device degradation. [145][146][147][148][149][150][151][152][153][154][155] In summary, the main effects of radiation damage in GaN-based HEMTs can be noted as follows:…”
Section: Ecs Journal Of Solid State Science and Technology 5 (2) Q35mentioning
confidence: 99%
“…2,[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154] The majority of deep electron traps in GaN are most likely dislocation-related and that probably explains the prominent role of dislocations in the trapping, gate leakage, subthreshold current leakage, and degradation in AlGaN/GaN HEMTs. The gate leakage in AlGaN/GaN HEMTs seems to be promoted by open-core screw dislocations and, in InAlN/GaN Q48…”
Section: Changes In Gan-based Hemt Performance After Irradiationmentioning
confidence: 99%
“…For Mg-doped p-type GaN, the Fermi level pinning near Ec-(0.8-0.9) eV has also been reported. 115 For Fe-compensated semi-insulating GaN, both N vacancies and deep level defects were observed by DRCLS (depth-resolved cathodoluminescence spectroscopy) analysis after fast and thermal combined neutrons irradiation with fluences from 10 14 ), most of the lattice damage can be repaired under a high temperature annealing process at around 1000 C; however, a certain amount of optical and electrical damage remains. 113 In a general sense, neutron irradiation will degrade the device performance.…”
Section: à2mentioning
confidence: 99%
“…114 Neutron irradiation can also alter the resistivity or even cause type-reversion of the material. Compensation schemes have been identified for both p-type 115 and n-type 116 GaN when the neutron fluence exceeds 10 16 cm…”
Section: à2mentioning
confidence: 99%
“…[34] and for fast reactor neutrons in ref. [35]. For proton irradiation conductivity versus temperature, low frequency capacitance-voltage C-V measurements, admittance spectra measurements, photoinduced transient current PICTS [36] and current deep traps transient CDLTS [37] spectroscopy indicated that deep electron traps near E c -0.5-0.6 eV and deep hole traps with levels near E v +0.3 eV and E v +0.85 eV were introduced.…”
Section: Levels Of Radiation Defects In Ganmentioning
confidence: 99%